Collaborative Practice Models Between Nursing And Social Work Professionals: Effects On Patient Satisfaction And Continuity Of Care (The Review of Diabetic Studies, 2024)
Background: Increasing patient complexity and the influence of social determinants of health have intensified the need for integrated, interprofessional care models. Collaboration between nursing and social work professionals represents a core strategy for delivering holistic, patient-centered care, particularly during transitions across healthcare settings. However, evidence regarding the impact of these collaborative practice models on patient satisfaction and continuity of care remains fragmented.Objective: To systematically synthesize the available evidence on collaborative practice models involving nursing and social work professionals and to evaluate their effects on patient satisfaction and continuity of care.Methods: A systematic review was conducted in accordance with PRISMA 2020 guidelines. Searches were performed in PubMed/MEDLINE, CINAHL, Scopus, and Web of Science. Eligible studies included peer-reviewed quantitative, qualitative, and mixed-methods research that explicitly examined collaborative models involving both nurses and social workers and reported outcomes related to patient satisfaction and/or continuity of care. Methodological quality was appraised using Joanna Briggs Institute (JBI) and CASP tools.Results: Fourteen studies published between 1994 and 2025 met the inclusion criteria. Across diverse healthcare settings—including acute hospitals, primary care, mental health services, and hospital-to-community transitions—collaborative nurse–social worker models were consistently associated with improved patient satisfaction, enhanced discharge preparedness, better care coordination, and stronger continuity of care. Several studies also reported reductions in care fragmentation, improved follow-up adherence, and fewer preventable readmissions. Overall methodological quality ranged from moderate to high.Conclusion: Collaborative practice models between nursing and social work professionals demonstrate meaningful benefits for patient satisfaction and continuity of care. Integrating clinical and psychosocial expertise through structured collaboration supports safer care transitions and more patient-centered outcomes. Formalizing these models within healthcare systems may contribute to improved quality of care and health service performance.